Population control and economic development. - Ohlin, Göran (Paris, Development Centre of the Organisation for Economic Co-operation and Development, 1967)
The books discusses the economic development of the poor countries given their demographic factors of child birth rate, death rate in comparison with Latin America.
Bibliography: p. 133-138.
sju 25/01/2019
Loans
Keywords: Population; Birth control; Economic development